The Implementation of Hospital Management Information Systems Using Human, Organization, Technology, And Benefit Models at Dinda Hospital Tangerang - Airo Dhanaris Simorangkir; Supriyantoro Supriyantoro; Arrozi Arrozi (Journal of Multidisciplinary Academic, 2020)
The purpose of this research was to examine the results of the implementation of hospital management information system using the HOT-Fit Model approach, so that it can be seen which variables (Human, Organization, Technology) have the most significant influence in improving the health service process in hospitals. The research was conducted in 3 (three) weeks using purposive sampling technique and an explanatory approach with using primary and survey data collection. The respondents were hospital employees who used the hospital information system. The population numbered 248 with a sample of 153. The data analysis was performed using the path analysis method. The results showed that there was simultaneous positive influence of human, organizational and technology variables towards net benefit. In singular, there was a positive influence of human variables on net benefits, organizational variables on net benefits, and technology variables on net benefits. The research findings indicated that human and organizational variables could not mediate technology variables towards the net benefit. Directly, the technology variable affects net benefit higher than the effect of technology on net benefit with human and organization variables as mediation. In depth interviews were also conducted to find out more about the problem and it was found that the human factor consisting of acceptance and knowledge of the hospital information system was the main problem.